O IPHAN e a invenção dos lugares de memória em Cuiabá : as demandas e políticas de preservação do patrimônio histórico (1958-2013) - Lacerda, Marina Duque Coutinho de Abreu (2014)
The present dissertation studies the heritage policies developed by the National Artistic and His-torical Heritage Institute (IPHAN) in the state of Mato Grosso, in order to identify the disputes and challenges imposed by the process of preservation, with a special emphasis on the city of Cuiabá. The period of the study starts in the beginning of the 1960 decade until the end of the first decade of the 21th century, having as the starting point the formation of a local preservation-ist consciousness, with the firsts debates about the process of statutory protection for the “Centro Historico” in the city of Cuiabá, and lasting until the establishment of the IPHAN Superintend-ence in the state of Mato Grosso, in 2009, and the preservation actions launched by the Plano de Aceleração do Crescimento (Grouth Acceleration Plan) aimed exclusively for civil engineering works on Historical Cities – “PAC das Cidades Históricas”.